(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article compares and contrasts American and English realism, two literary movements that emerged in the 19th century. Both movements share a commitment to portraying life and society realistically and addressing social issues. However, they differ in their geographical settings, cultural contexts, authors and works, and specific themes and styles. American realism focuses on the United States and often explores individualism and the American Dream, while English realism is centered in England and may delve into themes like social class, morality, and the impact of industrialization. The article highlights the similarities and differences between these two literary movements in terms of setting, cultural context, authors and works, and style and themes.